1989
DOI: 10.1080/00021369.1989.10869827
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Second Thermostable Purine Nucleoside Phosphorylase inBacillus stearothermophilusJTS 859

Abstract: The isoelectric point was 5.3. The Michaelis constants for inosine, guanosine, and adenosine were 0.22, 0.34, and 0.075 mM, respectively. The optimal temperature of the reaction was 70°C. The enzyme was stable at 70°C. Although other reported purine nucleoside phosphorylases were SH-enzymes, ,PUNPII was not a SH-enzyme because the enzyme reaction was not inhibited by PCMB and iodoacetic acid, the optimal pH of the enzyme reaction was from 7.0 to 11.0, and the enzyme did not contain cysteine. PUNPII and PUNPI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hexameric PNPs are prevalent in prokaryotes and exhibit a broader range of substrates. In some microorganisms, such as Escherichia coli and Bacillus spp., both a trimeric and a hexameric form of PNP are found (Seeger et al, 1995;Senesi et al, 1976;Hori et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Hexameric PNPs are prevalent in prokaryotes and exhibit a broader range of substrates. In some microorganisms, such as Escherichia coli and Bacillus spp., both a trimeric and a hexameric form of PNP are found (Seeger et al, 1995;Senesi et al, 1976;Hori et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…The other members of family I, mammalian PNPs, have a trimeric structure and are specific for 6-oxopurine ribonucleosides only. In some microorganisms, such as E. coli and Bacillus subtilis, both trimeric and hexameric forms of PNP are found (Seeger et al, 1995;Senesi et al, 1976;Hori et al, 1989). An alignment of the amino-acid sequences of several representatives of both types of PNP is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization Pu-NPase II showed that the enzyme closely resembled the second type of nucleoside phosphorylase isolated from B. stearothermophilus JTS 859. 18 ) Thus we concluded that the cloned punB gene encoded the Pu-NPase II.…”
mentioning
confidence: 99%